العلاقة بين نوع مركز الضبط والاكتئاب لدى مريضات سرطان الثدي في اللاذقية - داوود لبنه; بركات فارس (Latakia University Journal -Medical Sciences Series, 2017)
أجريت هذه الدراسة بهدف تقييم العلاقة بين نوع مركز الضبط ودرجة الاكتئاب عند مريضات سرطان الثدي،في مركز المعالجة الكيميائية والشعاعية في مشفى تشرين الجامعي بمحافظة اللاذقية في الفترة الواقعة بين 15/12/2015 وحتى 15/2/2016. وشملت الدراسة الحالية (100) مريضة سرطان ثدي. تم استخدام ثلاث أدوات، وتم ملء الأداة الأولى وهي استمارة البيانات الديموغرافية والاكلينكية من قبل الباحثثم تم الطلب إلى جميع المريضات المشاركات في الدراسة الإجابة على الأداة الثانية (مقياس مركز الضبط لروتر) والأداة الثالثة (مقياس بيك الثاني للاكتئاب).وأهم النتائج التيتوصلت الدراسة إليها وجود علاقةدالة إحصائياً بين نوع مركز الضبط ودرجة الاكتئاب عند مريضات سرطان الثدي، حيث أن أكثر من نصف مريضات سرطان الثدي من أفراد عينة الدراسة مصابات بالاكتئاب ولديهن مركز ضبط خارجي، لذا يقترح بإجراء دراسة لتأثير برنامج تدريبي لتعديلنوع مركز الضبط على معدل حدوث الاكتئاب عند مريضات سرطان الثدي. This study aimed to assessing the relationship between locus of control and depression among breast cancer patients. The study was carried out in the chemical and radiational treatment center in Tishreen University Hospital – Latakia, Data collected from15/12/2015 to 15/2/2016.The sample comprised of 100 breast cancer patients. Three tools was been used, the first tool (Demographic and Clinical Data Sheet) was been filling by the researcher, then all patients which participated in the study was asked to answer on the second tool (Rotter’s Locus of control Scale) and the third tool (Beck Inventory Scale II). This study found that there was significant statistical relation between locus of controltype and depression degree among breast cancer patients, more than half of breast cancer patients was had depression, and was had external locus of control. So it is recommended study theeffect of training program to modify locus of control type on the incidence average of depression among breast cancer patients.